2018
DOI: 10.1002/glia.23548
|View full text |Cite
|
Sign up to set email alerts
|

The guanine nucleotide exchange factor Vav3 modulates oligodendrocyte precursor differentiation and supports remyelination in white matter lesions

Abstract: The tightly controlled processes of myelination and remyelination require the participation of the cytoskeleton. The reorganization of the cytoskeleton is controlled by small GTPases of the RhoA family. Here, we report that Vav3, a Rho GTPase regulating guanine nucleotide exchange factor (GEF) is involved in oligodendrocyte maturation, myelination and remyelination. When Vav3 was eliminated by genetic recombination, oligodendrocyte precursor cell (OPC) differentiation toward mature oligodendrocytes was acceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 80 publications
(125 reference statements)
0
26
0
Order By: Relevance
“…When Vav3 is absent, this GABAergic wiring is not properly established, leading to the loss of the tonic inhibition exerted by the ventral over the rostral area of the ventrolateral medulla, and the development of multiple sympathetic-dependent physiological defects in mice [111,114,125,126]. Further functions of Vav3 inside the nervous system include the blockage of the differentiation of oligodendrocyte precursors and the promotion of myelination processes during both development and injury recovery [127]. Outside the central nervous system, Vav3 has been linked to the regulation of the differentiation of progenitor cells during the development of the mouse retina, the permeability of endothelial cells, the maturation of osteoclasts, and the regulation of antifungal innate immunity [95,128,129,130].…”
Section: Physiological Rolesmentioning
confidence: 99%
“…When Vav3 is absent, this GABAergic wiring is not properly established, leading to the loss of the tonic inhibition exerted by the ventral over the rostral area of the ventrolateral medulla, and the development of multiple sympathetic-dependent physiological defects in mice [111,114,125,126]. Further functions of Vav3 inside the nervous system include the blockage of the differentiation of oligodendrocyte precursors and the promotion of myelination processes during both development and injury recovery [127]. Outside the central nervous system, Vav3 has been linked to the regulation of the differentiation of progenitor cells during the development of the mouse retina, the permeability of endothelial cells, the maturation of osteoclasts, and the regulation of antifungal innate immunity [95,128,129,130].…”
Section: Physiological Rolesmentioning
confidence: 99%
“…Yet a subsequent literature search suggested that Vav3, Vcam1, and Cdc14a were the most likely genes influencing NADP + concentrations. Vav3 (Chr3:109340653–109685698 bp; 48.13 cM; GRCm38) is a Rho GTPase regulating guanine nucleotide exchange factor (GEF) [ 91 ]. The Vav protein family, including Vav3, are key activators of the Card9/NF-κB pathway in immunity [ 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that Vav proteins are potential activators of Rho GTPase family members [7,8]. It has been reported that Vav3 strongly unfolds its nucleotide exchange activity with the targets RhoA and RhoG, whereas Rac1 is activated less efficiently, and Cdc42 not at all [6,8,38]. Interestingly, Vav3 has been found enriched in hippocampal synapses [39] and in hippocampal neuron axons after 5 days in vitro [22].…”
Section: Discussionmentioning
confidence: 99%